Octonary (O) Search Algorithm - Maheshwari, Bhavesh R (International Journal of Computer Sciences and Engineering, 2019)
Searching is the process of finding a given value position in a list of values. It is fundamental operation in computer science. It is achieved by different searching methods which require number of iterations to reach at desired piece of data. In this research paper, another octonary (o) search algorithm is developed to compare & make searching even faster than algorithms like sequential, binary, ternary, & quaternary search.